Hubungan Pembiayaan Bagi Hasil Terhadap Profitabilitas Perbankan Syariah di Indonesia - Priyono Puji Prasetyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Islamic banks have the function of providing financing services to debtors, including types of profit sharing and buying and selling financing. This financing is expected to influence the level of profitability of Islamic banks. Therefore, this study aims to investigate the relationship between profit sharing and selling financing on the profitability of Islamic banks in Indonesia. The population of this study includes all Islamic banks. At the same time, the research sample uses a purposive sampling design with a choice of 14 Islamic Commercial Banks (BUS). Profit-sharing financing is represented by mudharabah and musyarakah products, while buying and selling is represented by murabahah, salam, and istishna products. The data used in this study is the aggregated financial statements of BUS for the 2015-2019 period with panel data analysis test tools. The research findings show that murabahah and istishna' financing affect the probability of ROE. Meanwhile, mudharabah and musyarakah financing partially affect the probability of ROA. The simultaneous test of debt and equity-based financing affect ROE profitability. Recommendations in the subsequent research to increase the number of years of research observations to get a more comprehensive picture